2018
DOI: 10.1002/mrm.27114
|View full text |Cite
|
Sign up to set email alerts
|

Flow MRI simulation in complex 3D geometries: Application to the cerebral venous network

Abstract: The framework provides a versatile and reusable tool for the simulation of any MRI experiment including physiological fluids and arbitrarily complex flow motion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
31
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(34 citation statements)
references
References 26 publications
0
31
0
Order By: Relevance
“…Several specialized phantoms or simulators that complement the Bloch-Torrey equations, enabling simulation or calibration of advanced MR imaging techniques, have been proposed in the literature. For instance, Klepaczko et al 192 and Fortin et al 193 developed MRI simulators for magnetic resonance angiography (MRA) of the cerebral circulation. TOF MRA data simulated by Klepaczko et al 194 were used to generate ground-truth data for evaluating vascular segmentation algorithms.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…Several specialized phantoms or simulators that complement the Bloch-Torrey equations, enabling simulation or calibration of advanced MR imaging techniques, have been proposed in the literature. For instance, Klepaczko et al 192 and Fortin et al 193 developed MRI simulators for magnetic resonance angiography (MRA) of the cerebral circulation. TOF MRA data simulated by Klepaczko et al 194 were used to generate ground-truth data for evaluating vascular segmentation algorithms.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…TOF MRA data simulated by Klepaczko et al 194 were used to generate ground-truth data for evaluating vascular segmentation algorithms. Fortin et al 193 extend the JEMRIS simulator to be able to produce flow-related MRA images for the main three techniques, viz., TOF MRA, phase contrast MRA, and contrast enhanced MRA. Pannetier et al 195 developed a simulator to predict dynamic contrast enhancement in MRI with bolus tracking.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…Last but not least, there is no simulation standard today within the MR field. A variety of MR simulators have been published in the literature to date, but they have mainly been developed and utilized for specific MR applications and they have not been validated extensively over a wider range of MR applications [17, 18].…”
Section: Introductionmentioning
confidence: 99%
“…For technical reasons, the AIF cannot be quantified directly but is usually estimated in the left ventricle (LV) . Computational fluid dynamics (CFD) simulations—as they have been widely used for general interpretation of perfusion MRI data—have shown that the CA bolus experiences dispersion during its passage through the epicardial vasculature toward the myocardial region of interest . This widening is erroneously attributed to the microcirculation, and therefore leads to a systematic underestimation of the MBF and an overestimation of the MPR values.…”
Section: Introductionmentioning
confidence: 99%